Model Development of Classification of Homogeneous Class Learning in Aquatic. (March 2017) - Firmansyah, H; Wahyudi, A; Wibowo, R
Abstract: Grouping is based on the view that in addition to these students have in common, also have differences. Grouping is the convergence of teaching classical system and individual system. Rapid development so that students do not interfere with a slow student and vice versa (students who do not interfere with rapid slow), then perform the grouping students. The purpose of this study was to determine whether the use of grouping students in learning strategies aquatic activities have an effect on student learning outcomes. Data analysis make two different test Mean Dependents (t test difference average Group Two pairs). RnD research methods with the length of study for 3 years. Participants in this study were students FPOK UPI that follows the course of learning aquatic. Results (year 1), with peer teaching methods to increase the participation and cooperation grouping (affective), mutual learning (cognitive) and skills (psychomotor) students.